Role of leisure and sleep in promoting daily physical activity in adults with down syndrome - Melissa R. Jenkins; Victoria L. Fleming; Emily K. Schworer; Yiwen Dong; Dana L. Tudorascu; Benjamin L. Handen; Sigan L. Hartley (Health Psychology and Behavioral Medicine)
Background: Adults with Down syndrome (DS) are at an elevated risk of chronic health conditions (e.g. obesity, Alzheimer’s disease). Although physical activity can mitigate the effects of these conditions, adults with DS spend more time sedentary relative to the adult general population. This study examined how daily fluctuations in two lifestyle factors, sleep and leisure, affect physical activity in adults with DS.Method: For 7 days, a sample of adults with DS (N = 109) wore a GT9X ActiGraph accelerometer to collect movement and sleep data and completed a daily diary to record leisure engagement. Movement variables included time spent sedentary, in light physical activity, and in moderate-to-vigorous physical activity. Sleep variables included total sleep time (TST) and sleep efficiency (SE). Time spent in and total count of cognitively stimulating leisure (e.g. reading, experiential activities) and social leisure (e.g. visiting friends, attending club meetings) were based on 22 items from the Victoria Longitudinal Study activity questionnaire. Mixed linear models examined between – and within-person associations for sleep and physical activity, and leisure and physical activity. Models controlled for sociodemographics, day of week, and weekend (vs. weekday).Results: At the between-person level, more TST was associated with more time sedentary (ps < .05) and less physical activity (ps < .001). More SE was associated with less time sedentary (ps < .001) and more physical activity (ps < .05). At the within-person level, participants with more physical activity than typical predicted greater TST (and less SE) that night (ps < .01). More cognitively stimulating and social leisure were associated with more physical activity at the within-person level (ps < .05).Conclusions: Findings can inform health programs seeking to increase physical activity in adults with DS. Interventions should consider the function of sleep and leisure in everyday life for long-term sustainability of physical activity.